Social factors affecting the achievement of sporting excellence for football players - Abdulameer, Yusef (Journal of Physical Education, 2011)
This research aims to identify the relationship between Social and Alaguet results of some Baghdad football clubs for the first class . The sample of research (63) for player of the football clubs for the first degree of the participants in the leagne championship for the 2009 – 2010 season have been chosen randomly (lottery method) from three clubs , and by (21) for each club . The scale was applied as hud of social relations of the axes of social in teraction on the scale of the research sample also relied on the results achieved in the fist stage of the champions league for season 2009 – 2010 . The researcher concluded that social relations are among the factors affecting the achievement of sporting excellence for football player is not less important than the rest of the factors that can directly affect the level of sport